Mobile learning on hygiene awareness for kindergarten (Kidgienic) / Noor Hasnun Rohim - Rohim, Noor Hasnun (2019)
Learning is crucial to everybody regardless of their age. Education and technology are interconnected where technology has influence education nowadays. The same goes to hygiene awareness as prevention is better than cure. The problem faced by the teachers and parents are how to teach children the important of hygiene especially hand washing for younger kids. Therefore, this project is to propose an innovative way to assist and teach children how to wash hand properly through mobile learning using mobile technology. The objectives of this project are to identify the user requirements for Kidgienic mobile learning on hygiene awareness for kindergarten, to design, and to develop Kidgienic mobile learning on hygiene awareness for kindergarten. The scope of this project is kindergarten students aged 3 years old. They will learn steps needed for washing hands. This project used the ADDIE Model as the methodology approach to the development of Kidgienic mobile learning application. ADDIE Model is divided into five stages which are analysis, design, develop, implementation and evaluation. However, to develop Kidgienic mobile learning application, it only concentrates on three phases which are analysis, design and development. Android Studio has been used as main software to develop Kidgienic mobile application as well as Adobe Photoshop, Adobe After Effects, Adobe Premiere CC and Construct 2. As conclusion, Kidgienic mobile learning application may help students in learning the right steps for washing hands.